SITUATION OF THE SERVICE FIELD IN SAMARKAND REGION AND OPPORTUNITIES FOR FURTHER DEVELOPMENT OF THE FIELD (Marketing Journal, 2025)
This article analyzes the state of the service sector in the Samarkand region and examines its importance in ensuring socio economic development. The contribution of the service sector to the growth of the regionʼs gross regional product is analyzed, and proposals for the further development of the industry are developed.
Keywords: service sector; GRP; business environment; trends